2018
DOI: 10.1021/acs.orglett.7b03719
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Aminoimidazolones and Imidazolones by (3 + 2) Annulation of Azaoxyallyl Cations

Abstract: The first examples of (3+2) annulations between azaoxyallyl cations and cyanamides and nitriles to give the corresponding 2-aminoimidazolones and imidazolones is reported. Based on the isolation of unexpected imidate products with certain substrates, it is proposed that the reaction proceeds via fast kinetic O-alkylation followed by rearrangement to the thermo-dynamically favored 2-aminoimidazolones and imidazolones. The method was applied to the formal synthesis of the antihypertensive drug irbesartan (Figure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…In their paper the authors demonstrated that the protection of indole was crucial to obtain (+/-)-minfiensine 126. While this type of cycloaddition has been extended to alkynes, 137 most of the efforts mainly focused on the cycloaddition with dipolarophiles bearing a heteroatom in the double (C=O, C=N, C=S) or the triple (C≡N) bond, to form 132 [138][139][140][141][142] by reaction with an aldehyde or a ketone, 131 [143][144] by reaction with an isothiocyanate or 129 and 130 145 by reaction with a nitrile. These reactions are mainly performed in fluorinated solvents such as HFIP.…”
Section: Aza-oxyallyl Cations In [3+2]-cycloadditions and Recent Devementioning
confidence: 99%
“…In their paper the authors demonstrated that the protection of indole was crucial to obtain (+/-)-minfiensine 126. While this type of cycloaddition has been extended to alkynes, 137 most of the efforts mainly focused on the cycloaddition with dipolarophiles bearing a heteroatom in the double (C=O, C=N, C=S) or the triple (C≡N) bond, to form 132 [138][139][140][141][142] by reaction with an aldehyde or a ketone, 131 [143][144] by reaction with an isothiocyanate or 129 and 130 145 by reaction with a nitrile. These reactions are mainly performed in fluorinated solvents such as HFIP.…”
Section: Aza-oxyallyl Cations In [3+2]-cycloadditions and Recent Devementioning
confidence: 99%
“…Transition metal dialkylcyanamide complexes attract significant attention for the past decades due to structural features of NCNAlk 2 ligands, which is differ from those of conventional nitrile ligands NCR (R=Alk, Ar) . Moreover, coordinated dialkylcyanamides exhibit excitingly different reaction behavior as compared to the conventional nitrile ligands, and metal‐involving reactions of NCNR 2 ’s allow the atom‐economic synthesis of aminosubstituted five‐membered heterocycles, e. g. 5‐amino‐1,2,4‐oxadiazoles,, 5‐amino‐2,3‐dihydro‐1,2,4‐oxadiazoles,, 5‐aminotetrazoles, 2‐amionooxazoles, 2‐aminoimidazolones, and 1,2,4‐oxadiazol‐5‐imines, and six‐membered heterocycles, e. g. aminopyridines, and aminopyrimidines …”
Section: Introductionmentioning
confidence: 99%
“…With regard to [3 + 2] cycloaddition processes, azaoxyallyl cation intermediates were key players in syntheses of γ-lactams, [208] pyrroloindolines, [209a- [212] imidazolones, [213] thiazolidin-4ones, [214] and oxazolidin-4-ones. [215a-e] On the other hand, azaoxyallyl cations were three-atom components in [3 + 1] cycloadditions with sulfur ylides giving βlactams (Scheme 192).…”
mentioning
confidence: 99%